Alanine with the Precipitate of Tomato Juice Administered to Rats Enhances the Reduction in Blood Ethanol Levels - Shunji Oshima; Sachie Shiiya; Yoshimi Tokumaru; Tomomasa Kanda (Journal of Nutrition and Metabolism)
Delay in gastric emptying (GE) lowers the blood ethanol concentration (BEC) after alcohol administration. We previously demonstrated that water-insoluble fractions, mainly comprising dietary fiber derived from many types of botanical foods, possessed the ability to absorb ethanol-containing aqueous solutions. Furthermore, there was a significant correlation between the absorption of ethanol and lowering of BEC because of delay in GE. Here we identified dietary nutrients that synergize with the water-insoluble fraction of tomatoes to lower BEC in rats. Consequently, unlike tomato juice without alanine, tomato juice with 5.0% alanine decreased BEC depending on the delay in GE and mediated the ethanol-induced decrease in the spontaneous motor activity (an indicator of drunkenness). Our findings indicate that the synergism between tomato juice and alanine to reduce the absorption of ethanol was attributable to the effect of alanine on precipitates such as the water-insoluble fraction of tomatoes.